(untitled) (International Journal of Medical and Surgical Sciences, 2017)
Irritation fibroma are the most common form of reactive lesions found within the oral cavity. These lesions normally attain a small size and show a slow growth rate. This paper reports a case of gigantic intraoral irritational fibroma with a history of rapid growth. Complete excision was performed and the specimen was sent for immunohistochemistry (IHC) staining. It was found positive for vimentin, hence reported as irritation fibroma.